Nutrition for young athletes - Volpe, Stella; Zimnowski, Tom ([S.l.] : University of Massachusetts Amherst, 2000)
This program explains the importance of eating well and walks you through the Food Guide Pyramid.
Executive producer, Norman D. Aitken ; editor, Christ Golas